Mild regiospecific alcoholysis and aminolysis of epoxides catalyzed by zirconium(IV) oxynitrate - Shinde, Sandip S.; Said, Madhukar S.; Surwase, Trupti B.; Kumar, Pradeep (Tetrahedron Letters, 2015)
A regiospecific method for the ring-opening reaction of epoxides by the primary, secondary, tertiary alcohols, and aryl, aliphatic amines has been developed using non-toxic metal nitrate salt as a catalyst. The best results were obtained using zirconium(IV) oxynitrate among the various screened metal nitrate salts. The reported protocol works efficiently for styrene epoxide and aliphatic as well. (C) 2015 Elsevier Ltd. All rights reserved.
Keywords: Alcoholysis; Aminolysis; Epoxide; Lewis acid; Zirconia

Molybdenum oxide-mediated facile aliphatic nucleophilic fluorination - Said, Madhukar S.; Khandare, Leena; Shinde, Sandip S. (Tetrahedron Letters, 2017)

Metal-free, Tf2NH-catalyzed 1, 6-conjugate addition of imidazopyridine to para-quinone methides: easy access to C3-functionalized triarylmethane imidazopyridine - Khonde, Nilesh S.; Said, Madhukar S.; Sabane, Jagjivan K.; Gajbhiye, Jayant M.; Kumar, Pradeep (Tetrahedron, 2021)
An inexpensive and commercially available Tf2NH-catalyzed 1,6-conjugate addition of imidazopyridine (IMPY) heterocycles to para-quinone methides (p-QMs) is reported. The present transformation provides a diverse class of C3-functionalized triarylmethanes heterocyclic derivatives of imidazopyridine. These metal-free transformations provided a very broad substrate scope of conjugate addition product with a high yield up to 97% within a short duration. (C) 2021 Elsevier Ltd. All rights reserved.
Keywords: 1; 6-Conjugate addition; Bronsted acid; C3-functionalization; Imidazopyridine; para-Quinone methide